Effect of dietary starch inclusion, feeding level and their combination on nutrient digestibility, bile acid balance, faecal waste production and characteristics of yellowtail kingfish (Seriola lalandi) - Yaqing Zhang; Roel M. Maas; Peter Horstmann Zuther; Jeroen Kals; Satya Prakash; Thomas W.O. Staessen; Fotini Kokou; Johan W. Schrama (Aquaculture Reports)
The effect of dietary starch content, feeding level and their interaction on nutrient digestibility, bile acid balance, faecal waste production and characteristics were investigated in yellowtail kingfish (Seriola lalandi). The effect of starch inclusion level was tested in a dose-response trial, using five diets differing in the inclusion level of gelatinized wheat flour (WF) (0, 4, 8, 12 and 16 %) and thus starch level. Each diet treatment was tested in triplicates. A restricted feeding period of 4-wk was followed by a 2-wk period of satiation feeding. Results showed that both starch inclusion level and feeding level (restricted vs. satiation) negatively affected macronutrient digestibility, with fat digestibility being most affected. The latter was associated with a potential depletion of the body bile acid pool as bile acid balances (bile acid intake – faecal bile acid loss) were consistently negative for all diets during both feeding periods. Faecal bile acid loss increased with both increasing feeding level and increasing dietary starch level, which was mainly caused by increased faecal waste production. Furthermore, starch had a negative impact on faecal characteristics. High dietary starch levels resulted in increased faecal waste production, and higher amounts of non-removed faeces by settling due to reduced faecal removal efficiency. The critical dietary starch content was estimated to be 6 %. Above a 6 % dietary starch content, fat digestibility and faecal removal efficiency decreased, while non-removed faeces increased with the dietary starch content. When culturing yellowtail kingfish in RAS, dietary starch levels should be below 6 % from a digestion as well as faecal management point of view.